e-Pontos: Uma solução embarcada de automação comercial aplicada a clubes de fidelidade baseado em tecnologia RFID e esmart card - Paiva, Jailton Carlos de (2012)
In practically all vertical markets and in every region of the planet, loyalty marketers have adopted the tactic of recognition and reward to identify, maintain and increase the yield of their customers. Several strategies have been adopted by companies, and the most popular among them is the loyalty program, which displays a loyalty club to manage these rewards. But the problem with loyalty programs is that customer identification and transfer of loyalty points are made in a semiautomatic. Aiming at this, this paper presents a master's embedded business automation solution called e-Points. The goal of e-Points is munir clubs allegiances with fully automated tooling technology to identify customers directly at the point of sales, ensuring greater control over the loyalty of associate members. For this, we developed a hardware platform with embedded system and RFID technology to be used in PCs tenant, a smart card to accumulate points with every purchase and a web server, which will provide services of interest to retailers and customers membership to the club